2001
DOI: 10.1254/jjp.87.195
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Spatial Learning Performances in Lipopolysaccharide-Treated Mice

Abstract: ABSTRACT-It is well demonstrated that acute or chronic stress leads to reduction of learning ability. Lipopolysaccharide (LPS), a component of the outer membrane of gram-negative bacteria, induces profound physiological and behavioral changes, including fever, decrease in food motivation, and decrease in social behavior. These changes might be interpreted as an acute stress reaction to the LPS. In the present study, therefore, we investigated the effects of LPS (400 -800 mg/ kg, i.p.) on spatial learning perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 23 publications
5
74
3
2
Order By: Relevance
“…(22,23) The mice were placed on a metal mesh (mesh dimensions 180 mm wide  120 mm deep, 6-mm intervals) and allowed to grasp the wire gauzes by the forelimbs and hind limbs. Then the tail was pulled backward horizontally until the mice released the gauzes so that the maximal force was recorded.…”
Section: Measurement Of Grip Strength and Muscle Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…(22,23) The mice were placed on a metal mesh (mesh dimensions 180 mm wide  120 mm deep, 6-mm intervals) and allowed to grasp the wire gauzes by the forelimbs and hind limbs. Then the tail was pulled backward horizontally until the mice released the gauzes so that the maximal force was recorded.…”
Section: Measurement Of Grip Strength and Muscle Weightmentioning
confidence: 99%
“…Many studies have revealed that a measurement of grip strength is a convincing method for assessing muscle strength in vivo. (22,23,25,26) Therefore, in this study we measured grip strength as described under ''Materials and Methods.'' Because there is positive correlation between body weight and grip strength, the data on maximum grip strength divided by body weight were evaluated.…”
Section: Effects Of Fgf-23ab On Grip Strengthmentioning
confidence: 99%
“…For this reason, LPS are commonly employed to mimic bacterial infections in experimental animals. The systemic inflammation mediated by the LPS can trigger a set of cellular and molecular events that are able to initiate neuroinflammation to affect cognitive function (Arai et al 2001;Cunningham et al 2009;Sparkman et al 2006) and reduce adult neurogenesis (Fujioka and Akema 2010;Monje et al 2003). It has been well documented that pregnant animals have an increased sensitivity to LPS compared to non-pregnant ones (Faas et al 2003;Kunnen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As evidence, a consistent animal literature shows peripheral IL-6 (whether the result of exogenous administration or in vivo immune challenge) to be associated with increased levels of cytokines in the hippocampus, where IL-6 and IL-6 receptors are expressed abundantly (6)(7)(8). Further, in several animal models, increased levels of hippocampal IL-6 interfere with long-term potentiation (9)(10)(11), neurogenesis (12), and neural plasticity (13,14), which can all impair performance on hippocampal-dependent learning and memory tests (13,(15)(16)(17). Conversely, IL-6 receptor antagonists prevent inflammation-related disruption of hippocampal LTP and ensuing cognitive sequelae (18).…”
Section: Introductionmentioning
confidence: 99%